Attitudes Towards Environmental Protection in International Comparative Research - Rydzewski, Pawel (Problemy Ekorozwoju, 2024)
Protection of the natural environment is one of the key areas of sustainable development strategy. However, even the best strategy needs support from society. Drawing upon the data from the International Social Survey Program - Environment 2019-2023, we analysed environmental attitudes among residents of 28 countries. 45.7% of respondents declare their concern about issues related to the natural environment. Over half (55.6%) believe in making personal sacrifices, such as incurring additional costs or spending more time, to benefit the environment. 39.7% declare that they avoid purchasing certain products for environmental reasons (always and often). Approx. 19% of respondents have signed an environmental petition and approx 15% have given money for the environmental purpose in the last 5 years. Most respondents (over 40%,) believe that educating people about the benefits of environmental protection is the most effective way to encourage individuals and families to adopt environmentally responsible behaviours. Fewer respondents (35%) believe that this can be done through the tax system or by imposing fines on those who damage the environment (approx. 23%). The ISSP does not explicitly address global challenges of the last years, i.e. the COVID-19 pandemic and the war in Ukraine.. However, by comparing people’s recent attitudes with those in the past, we can see the impact of the pandemic and war on environmental